Comparison of kinematic performance and analysis of the effect of punching speed of rear hook of college boxers of different sexes - Xu, Q.; Xi, C.; Mao, R. (International Journal of Performance Analysis in Sport, 2024)
The paper aims to compare the kinematic performance of the rear hooks of college boxers of different sexes and analyse the influence of the kinematic indexes on punching speed. Thirteen kinematic indexes were selected to analyse the rear hook of male (n = 20) and female (n = 20) college boxers through a three-dimensional framework and high-speed camera. Additionally, a stepwise multiple linear regression equation was established to analyse the influence of these parameters on the maximum punching speed. The results revealed that the rear hook punching speed of college male boxers was 26% faster than that of female boxers. Also, there were statistically significant differences in the maximum angular velocity of the shoulder joint, hip joint angle, and knee joint angle (p < 0.01). In addition, the differences between their X- and Y-axis centre of gravity positions were statistically significant (p < 0.01). Moreover, the multiple regression analysis revealed that the maximum shoulder velocity was the most influential factor in the maximum punching speed of the rear hooks for both male and female boxers. This study provides recommendations for the daily training of college boxers and their coaches, to develop targeted training interventions for the rear hook.